Symbiotic Organisms Search: A new metaheuristic optimization algorithm - Cheng, Min-Yuan; Prayogo, Doddy (Computers & structures, 2014)
•A new SOS algorithm is introduced to solve engineering optimization.•Twenty-six mathematical problems and five engineering design problems are tested.•The results obtained by SOS are compared with other optimization methods.•Obtained results confirm the excellent performance of the SOS method. This paper applies a new robust and powerful metaheuristic algorithm called Symbiotic Organisms Search (SOS) to numerical optimization and engineering design problems. SOS simulates the symbiotic interaction strategies adopted by organisms to survive and propagate in the ecosystem. Twenty-six unconstrained mathematical problems and four structural engineering design problems are tested and obtained results compared with other well-known optimization methods. Obtained results confirm the excellent performance of the SOS method in solving various complex numerical problems.